Performance criteria for para-athletes in fencing - Marsan, T.; Landon, Y.; Navarro, P Watier, B. (Sports Biomechanics, 2024)
Wheelchair fencing is an opposition sport on a specific wheelchair, with a fixed distance between the two athletes. As for other Paralympic sports, different categories exist for the different pathologies of the athletes. Searching for biomechanical performance criteria is of primary interest for coaches, recruiters and trainers. Such performance criteria have been highlighted for able-bodied fencers but not for para-fencers. Through transposition, the corresponding parameters for para-fencers would be the weapon speed and the ability to move the trunk forward and backward on their wheelchair. Therefore, the objective of this study was to determine performance criteria for para-fencers. Eleven French para-fencers performed fencing activities with a motion capture system while facing each other, with their own equipment. Different activities were realised to quantify the allonge, the weapon speed, and the torso motion. Only the correlation between the range of motion of the torso and the mass of the athletes wielding an épée was significant (p = 0.02). The comparison between the different categories showed significant differences for the torso motion, which was not found for the weapon speed. Future studies, with a larger cohort, might help validate, or not, tendencies found in this study.